Caracterização da microbiota antagonista em biofertilizantes e seu papel nas interações multitróficas para o manejo do Meloidogyne exigua em cafeeiro arábica - Côgo, Adan Dezan (2020)
Phytonematoids are among the main pathogens in the Arabica coffee culture, in which the species Meloidogyne exigua gains prominence. Due to the complexity of handling in the field and the high toxicity of chemicals that target its management, alternative techniques have been investigated to reduce the population of this pathogen in the field. Among the alternatives, the use of low toxicity nematicides and the application of biological products as biofertilizers have recently gained prominence in the management of gall nematodes. However, due to the great diversity of microorganisms present in these formulations of biofertilizers, it is necessary to carry out the morphological and genetic characterization in order to understand the genetic diversity. The aim of this study was to access the genetic diversity of microorganisms present in biofertilizers used for the management of M. exigua; and to evaluate the isolated and combined effect of different chemical nematicides and biofertilizers in the management of M. exigua in commercial Arabica coffee plantations in the region of Iúna, southern Espírito Santo. The isolates were obtained from serial dilutions of biofertilizers in different culture media for further visual analysis of morphological characteristics. For the genetic characterization, Rep-PCR was performed using REP, ERIC and BOX primers. The agarose gels were photographed and later analyzed in the GelJ program, in which the similarities between the digitized profiles were calculated using the Jaccard Similarity Coefficient (CSJ), and based on the estimates of dissimilarities of the isolates were grouped by the UPGMA hierarchical method. In the field, chemical nematicides and biofertilizers were applied alone and combined and population measurements of M. exigua were carried out before application and 45 days after application of the products. From Vitaflex and Maxfert, 218 bacteria were isolated and included in 53 groups. Of this total, 40 groups were found in both biofertilizers and 13 groups present only in Vitaflex. In the field, the isolated application of Nimitz, Vitaflex and Maxfert resulted in a greater population reduction of M. exigua. The combination of biofertilizers with Nimitz also showed satisfactory results, making it possible to combine these products for the management of M. exigua in the field